Basilius Hyacinthius’ Panegyricus (Padua, 1580): Historical and Literary Sources and Contexts - Antanavičius, Darius (Senoji Lietuvos literatūra, 2020)
Basilius Hyacinthius’ Panegyricus in excidium Polocense (hereinafter Panegyricus) is the first book to have been written and published by a resident of Vilnius in the territory of present-day Italy. The aim of the paper is to determine the background of Panegyricus and the historical sources, which the author resorted to in writing the book, and to reveal its literary sources and influences.In the absence of any other sources, the circumstances of the work’s creation can only be inferred from the author’s own words in the dedication. In it, he mentions that his information on the course of the 1579 Polotsk campaign was provided by his friends’ letters from Lithuania, the vivid stories of travellers who had come to Italy, and by some ‘writings’.The author of the Panegyricus had at hand and relied mainly on the official printed source of the 1579 Polotsk campaign: ‘The King’s ordinance (on the celebration) of Holy Mass for the achieved victory over Muscovy’ (Edictum regium de supplicationibus ob rem bene adversus Moschum gestam). Other sources included the aforementioned letters sent by friends and informing about the circumstances of the 1579 campaign; these must have been accompanied by some manuscript material, such as a list of the noblemen of the Grand Duchy of Lithuania, who hired soldiers at their own expense and brought them to the military camp; the list took more than 100 lines of the poem. The last group of sources consisted of the poet’s own first-hand information about people and facts that, although unrelated to the story of the Polotsk campaign, were woven effectively into the poem. To sum up Basilius Hyacinthius’ sources and their use, he did not use or indicate any unknown sources or facts that would shed more light on the history of the 1579 Polotsk campaign. The author of the poem, however, did not set such an aim to himself: his main task was to glorify King Stephen Bathory and his homeland Lithuania.At the level of the structure of the work and its individual segments, there is little emulation of the ancient Roman authors of epics or other bards. The author took the traditional motif of Fame, the Fame that announces the achieved victory over Muscovy to the whole world; Muses are also addressed several times. Following the example of the ancient Roman epic and other authors, conventional adhortations were used. Based on the poets of Antiquity, the greeting of the Nereids, the goddesses of river, was also introduced. The intervention of the gods in a Christian spirit to save the warriors from mortal danger and the insertion of the dream of Stephen Bathory foretelling the pending battle should be related to the epic authors, in particular Virgil. In different variations, all of this is found in the epics of ancient Rome.The strongest influence of the classical Roman poets is observed at the lexical level of the poem. Basilius Hyacinthius relied mostly on Virgil, especially his Aeneid, as the benchmark for all poets writing in Latin hexameters. The work of the author from Vilnius is permeated with Virgil’s words, especially in the second half of the poem, when the author tries to compensate for the lack of factual historical material by using more and more of the vocabulary of this ancient Roman bard.The poem under analysis was not the only poetic work to commemorate the recapture of Polotsk. Two other works significant in their scope and ambition – Daniel Hermann Stephaneis Moschovitica and Samuel Wolff’s Stephani Primi serenissimi Poloniae regis et magni Lituanorum ducis etc. adversus Iohannem Basilidem, magnum Moscoviae ducem, expeditio carmine elegiaco descripta (The Campaign of Stephen the First against Ivan Vasilyevich, Grand Duke of Muscovy) – were published between 1582 and 1583. Both authors were united in their desire to chronicle all of Stephen Bathory’s wars against Ivan IV. Wolff succeeded in completing it: his poem includes the Pskov campaign of 1581.Neither Hermann nor Wolff took part in the Polotsk campaign and, like Basilius Hyacinthius, relied mainly on official printed information – the aforementioned ‘King’s Ordinance’.From the literary point of view, the three main bards of the march of Polotsk (Hyacinthius, Hermann, and Wolff) demonstrated more or less the same level. None of the three works is a literary masterpiece and will never be; nonetheless, they fully conform to the context and trends of neo-Latin writing of the second half of the sixteenth century. The distinctive feature of Basilius Hyacinthius’ work is the transparent desire to emphasise the contribution of the Lithuanian nobility to the retaking of Polotsk, after having highlighted the merits of Stephen Bathory himself, and to counterbalance, at least to a certain extent, the well-organised glorification of the victory of the Polish arms by the king’s entourage. Basilius Hyacinthius’ personal determination and ability to become the first bard of the recapture of Polotsk abroad is noteworthy and much appreciated.
Keywords: Pranciškus Gradovskis (Franciszek Gradowski); Basilius Hyacinthius; Daniel Hermann; imitation and emulation; Jan Kochanowski; neo-Latin literature; Ovid and his reception; recapture of Polotsk in 1579; Stephen Bathory; Andrzej Trzeciecki; Virgil and his reception; Samuel Wolff